Potential Benefits and Challenges of Generative Artificial Intelligence (AI) Tool, ChatGPT - Faheemudin; Sarala Thulasi Palpanadan; Ros Eliana (Development in Language Studies, 2025)
The study proposes the potential benefits and challenges of the Generative-AI tool, ChatGPT, for learning writing skills in educational sectors. The study thematically compares and evaluates 26 research articles published in Science Direct and Springer Open from 2023 to 2025. It offers a systematic literature review to compile, integrate and analyze the available data. The articles are divided into two categories: category A) potential benefits (CA) and category B) challenges of ChatGPT (CB). Each category covers three to four themes found in these articles. CA presents that ChatGPT assists its users through ‘feedback’, ‘writing skills’, and ‘personalized learning’. Whereas CB discusses the challenges and limitations of ChatGPT in the form of four themes: ethical consideration’ of AI tools by the researchers, its disruptive impacts on ‘critical thinking’, and it can cause impairment of ‘creativity’ and ‘academic integrity’—furthermore, the proposed major themes present sub-themes which cover several other promises and drawbacks of ChatGPT. Keeping in view the proposed categories and themes, the study concludes that the Generative-AI tool, ChatGPT, facilitates its users on a larger level and may not be overlooked due to its requirement in different sectors, especially in educational institutions, for learning writing skills.